Analysis of multidrug resistant group B streptococci with reduced penicillin susceptibility forming small, less hemolytic colonies. - Hirotsugu Banno; Kouji Kimura; Yosuke Tanaka; Tsuyoshi Sekizuka; Makoto Kuroda; Wanchun Jin; Jun-Ichi Wachino; Keiko Yamada; Keigo Shibayama; Yoshichika Arakawa (PLoS ONE)
Group B streptococci (GBS; Streptococcus agalactiae) are the leading cause of neonatal invasive diseases and are also important pathogens for elderly adults. Until now, nearly all GBS with reduced penicillin susceptibility (PRGBS) have shown β-hemolytic activity and grow on sheep blood agar. However, we have previously reported three PRGBS clinical isolates harboring a CylK deletion that form small less hemolytic colonies. In this study, we examined the causes of small, less hemolytic colony formation in these clinical isolates. Isogenic strains were sequenced to identify the mutation related to a small colony size. We identified a 276_277insG nucleic acid insertion in the thiamin pyrophosphokinase (tpk) gene, resulting in premature termination at amino acid 103 in TPK, as a candidate mutation responsible for small colony formation. The recombinant strain Δtpk, which harbored the 276_277insG insertion in the tpk gene, showed small colony formation. The recombinant strain ΔcylK, which harbored the G379T substitution in cylK, showed a reduction in hemolytic activity. The phenotypes of both recombinant strains were complemented by the expression of intact TPK or CylK, respectively. Moreover, the use of Rapid ID 32 API and VITEK MS to identify strains as GBS was evaluated clinical isolates and recombinant strains. VITEK MS, but not Rapid ID 32 API, was able to accurately identify the strains as GBS. In conclusion, we determined that mutations in tpk and cylK caused small colonies and reduced hemolytic activity, respectively, and characterized the clinical isolates in detail.